Rock and Mineral (E. Explore) - Farndon, John (London Dorling Kindersley, 2005)
A book and a website in one! From rocks that have been flung from erupting volcanoes and stalactites as old as the dinosaurs to spectacular crystal formations and precious nuggets of gold and platinum, explore the history of our planet. Read about how the rocks beneath your feet were formed and then go online with Google to discover more. All the websites are safe and appropriate and have been specially selected to give you all the latest and best information.
Include Colored Ilustrations and Maps.
An introduction to rocks and minerals using 3-D models, data boxes, charts, and maps, covering topics from the history of geology to minerals in the home.
Keywords: Rocks -- Mineralogy